Egyptian coup of 2013: an 'econometric' analysis. Issue 3 (26th May 2016) - Korotayev, Andrey; Issaev, Leonid; Shishkina, Alisa
ABSTRACT: The article is devoted to an 'econometric' analysis of the events in Egypt that happened in summer 2013. The analysis of the Egyptian Stock Exchange indices suggests that the 2013 Egyptian coup d'état was prepared to a very considerable extent by the reconciliation between the Egyptian economic and military elites. It also suggests some additional hints regarding the split between the Arabian monarchies (Qatar, on the one hand, and Saudi Arabia, Kuwait and the United Arab Emirates on the other) that displayed itself during the Egyptian crisis.